2023
DOI: 10.3390/rs15215189
|View full text |Cite
|
Sign up to set email alerts
|

Solar Potential Analysis of Bus Shelters in Urban Environments: A Study Case in Ávila (Spain)

María Sánchez-Aparicio,
Enrique González-González,
Jose Antonio Martín-Jiménez
et al.

Abstract: The presence of shadows is one of the main disadvantages of photovoltaic solar panel installations in urban environments. This article analyses their effect on solar installations performed on urban elements where the use of solar energy can be considered novel: bus shelters. For this purpose, the PVGIS tool is used in combination with a new methodology for the extraction of the shadow horizon profile from LiDAR point clouds. The results show a 29.90% and 37% reduction of calculated solar radiation using horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The National Geographic Institute (IGN) in Spain offers highly accurate and updated LiDAR data of the entire Spanish territory, captured periodically under the National Plan for Territory Observation (Plan Nacional de Observación del Territorio—PNOT) [ 38 ]. Previous studies have demonstrated the applicability of these LiDAR data in urban environments in Spain [ 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The National Geographic Institute (IGN) in Spain offers highly accurate and updated LiDAR data of the entire Spanish territory, captured periodically under the National Plan for Territory Observation (Plan Nacional de Observación del Territorio—PNOT) [ 38 ]. Previous studies have demonstrated the applicability of these LiDAR data in urban environments in Spain [ 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%